Analysis of the Teaching Reform of Computer Courses in Higher Vocational Education under the New Background - Ma, Lijuan (Journal of Theory and Practice of Social Science, 2023)
Vocational colleges are an important battlefield for talent cultivation, and computer teaching is an important component of vocational colleges. With the development of information technology, computer technology has gradually penetrated into various industries, bringing great convenience to people's work and life. In this context, the teaching situation of computer courses in vocational colleges is also receiving increasing attention. As a computer teacher in vocational colleges, it is necessary to promptly analyze the problems and shortcomings in the current teaching of computer courses, and actively explore effective ways to improve and adjust teaching methods, in order to achieve the effect of improving the quality of computer course teaching in vocational colleges. Therefore, based on my own teaching practice, the author analyzed the teaching reform strategies for vocational computer courses in the new context, hoping to provide ideas and references for the development of teaching activities for colleagues.